Buying Behavior and Factors Influencing Decision on Shopping Products Imported from China - Meepheamphoonsri, Ajirapal; Charoenwiriyakul, Chandej; Siriwattana, Srochinee (International Journal of Development Administration Research, 2022)
This Article aimed to study 1) behavior, Level of brand image, marketing mix and decision on shopping products imported from China 2) Factors influencing consumers’ decision on shopping products imported from China. This is quantitative research. A sample were 400 people in Bangkok and have purchased products imported from China at least once. They was selected by purposive sampling, the instrument for collecting data was questionnaires. Analysis data by mean, standard deviation and multiple regression analysis.The research results were found as follows; 1) consumers’ behavior about type of imported products from China at the most were fashion clothes. The number of shopping products imported from China was 1-3 times per month. The average cost of shopping products imported from China was 501 – 1,000 baht each time. Oneself was the most important to consumers’ decision to shopping products imported from China. The main reason for shopping products imported from China was cheap and shopping from Shopee.2) factors influencing consumers’ decision on shopping products imported from China were brand image and marketing mix respectively. Findings from this research import business operators can use it in their business planning to be more efficient.